Can conformity overcome the yuck factor? Explaining the choice for recycled drinking water. (1st January 2020) - Leong, Ching; Lebel, Louis
Abstract: Of the 17 SDGS, the United Nations has recently revealed that countries are not on track to receive the water and sanitation goals by the deadline. As climatic events decrease the reliability of traditional drinking sources, especially in cities, recycled drinking water (RDW) is becoming an increasingly important policy option. Yet, the implementation of RDW remains mired in difficulties, with the psychological "yuck" factor as a key obstacle. Studies of successful cases of RDW implementation show that trust, information and social norms are important. However, no studies of RDW have directly compared the relative importance of information to the power of social norms. This paper explores the role of conformity, as a social norm, in increasing public acceptance of recycled water for drinking. Using a simple choice experiment, we find that conformity per se appears to provide sufficient reason for behavioural change relating to recycled water, rather than information or economic incentives. This study is one of the first to present empirical evidence from a choice experiment on RDW, and has practical implications on the use of conformity as motivation to taking difficult decisions.